STEAMPUNK AS A SOUND PHENOMENON IN CARTOONS - Stolbova P. A. (Vestnik Issyk-Kulʹskogo universiteta)
Steampunk is a subgenre of science fiction that includes retrofuturistic technology and aesthetics inspired by industrial steam engines of the 19th century. The soundtrack of the cartoon performs an important function in immersing the player in digital reality, familiarizing them with the world. The authors get the opportunity to present a better, integral project, an independent artistic solution that is as close to reality as possible. Thus, the visual style is complemented by a distinctive sound design. Such an example allows us to slightly change or expand the understanding and perception of the phenomenon. The image begins to sound, which means it acquires more realistic properties. The paper examines approaches to creating sound design in a certain style in order to determine the most profitable strategies for working on the sound design of a cartoon. The analysis of the works in order to determine the characteristic features of the style, that constitutes its sound features. Each element of the visual series has its own sound, which is born from movement or interaction. Key sources: gears that ensure the operation of mechanisms; automatic machines at the time of the task; train. The sound may be different in each individual case. The size of the object and the location affect the volume and intensity, which provides a difference in perception.